Revisiting Shimoda's “Shuuchaku-Kishitsu” (Statothymia): A Japanese View of Manic-Depressive Patients - Hitoshi Tsuda (Depression Research and Treatment, 2011)
Although the empiric paradigm is now dominant in academic research, in Japan quite a few psychiatric clinicians still take phenomenological-anthropological approaches into consideration, especially when they address manic-depressive illness with typical endogenous features. This is because Shimoda's concept of “shuuchaku-kishitsu” (statothymia) has been widely accepted, together with other phenomenological views of continental origin. In the present paper the author first delineates Shimoda's concept which is based on observations of patients' personality features and the characteristics of their emotionality. He then attempts to refine this concept in spatiotemporal terms, presenting the view that in patients the past self tends to adhere to the present self (the term “shuuchaku” means “adhering to” or “preoccupied with”). He also considers that patients tend to incorporate “soto” (outer space) into “uchi” (inner space), where they believe that symbiotic relations are preserved. Finally, he argues the clinical significance of the presented views in the cultural milieu in which Japanese psychiatric practices are situated.